Axial twisting within an ending loop of a continuous suture pattern affects the biomechanical properties of knots of certain suture sizes and types - Whyte, MacKenzie (Kansas State University, 2023)
Objective: To determine whether axial twisting within an ending loop of a continuous suture pattern negatively impacts security and maximum load to failure of suture knots. Samples: 525 knots (15 samples each of seven different suture types/sizes tested in five knot twist configurations each). Procedures: Each suture type and size were used to create a starting square knot and each of the following ending square knot configurations: 0 twists, 1 twist, 4 twists, and 10 twists. Each suture was tested to maximum failure using an Instron Universal Testing Machine with a 100 kg load cell at a speed of 100 mm/min. Each suture and knot was evaluated for mode of failure using gross evaluation of the knots and video footage recorded during testing. Results: Maximum load to failure was decreased in knots tied within ending loops containing more twists for some types and sizes of suture. All knots with 4-twists made using 0-PDO, 1 PDO, and 2-0 Nylon were more likely to fail at the knot than knots without twists. All knots containing 10 twists, except 3-0 Monoderm, were more likely to fail at the knot than knots without twists. Clinical Relevance: This study shows that for select suture types and sizes, increasing the number of twists present within the ending loop weakens the knot. Ideally the ending loop should be unraveled prior to tying the knot.
Keywords: Suturing; Knot tying; Square knots